Bahasa Seksis dalam Buku Al-Lughah Al-'Arabiyyah Al-Mu'asirah Karya Prof. Dr. Eckherad Schulz (Kajian Sosiolinguistik) - Devi Yaniar Wi Hargina (LPPM IAINU Kebumen, 2020)
This research aims to describe the existence of a form of sexist language in the book Al-Lughah Al-'arabiyyah Al-Mu'asirah by Prof. Dr. Eckherad Schulz. In this case, the researcher discusses the relationship between (gender differentiation) and the use of Arabic which has implications for sexist language in the book Al-Lughah Al-'arabiyyah Al-Mu'asirah by Prof. Dr. Eckherad Schulz using the method of discourse analysis (discourse analysis) as well as the theory of language and gender in sociolinguistic studies. The data sources of this research are in the form of quotations of words, sentences and discourses contained in the book.